Pneumatic drilling end effector - MARTINEZ ANTONIO B; WHINNEM ERIC; DAVANCENS ANGELICA; ZANTESON WILLIAM PAUL (2003)
A method of using a drilling end effector includes providing a drilling end effector having a plurality of photogrammetry targets secured thereto. The positional orientation of the drilling end effector along six degrees of freedom is detected using a photogrammetry sensor to determine the orientation of the plurality of photogrammetry targets and outputting a position signal to a controller. The drilling end effector is robotically manipulated adjacent to a part to be drilled in response to the position signal to accurately position a drill bit relative to the part to be drilled. The part is then drilled.